Respon Pertumbuhan dan Hasil Tanaman Wortel (Daucus carota L.) di Dataran Rendah pada Berbagai Volume Media dan Dosis Ampas Padat Biogas - M. Zaenuddin Syahril Sidiq; Aluh Nikmatullah; Herman Suheri (LPPM Universitas Mataram, 2020)
This study aimed to determine the growth responses and yield of carrot (Daucus carota L.) grown at the lowland at various rates of biogas solid waste and media volumes. The experiment was carried out at Mataram University experimental field in Narmada, West Lombok, NTB with an altitude of 136 m above sea level, from April to July 2019. The experiment was designed according a factorialy Randomized Completed Block Design (RCBD). The first factor consisted of 4 volumes of the media which i.e: 2000 cm3/20 x 20 cm, 4000 cm3/25 x 25 cm, 5000 cm3/30 x 25 cm and 7000 cm3/30 x 30 cm. The second factor consisted of 3 levels of biogas solid waste (bio-slurry) with i.e: 10 tons/ha, 15 tons/ha, and 20 tons/ha. These two factors were combined resulted in 12 treatment combinations. Each treatment was repeated so there was 36 experimental units each with replicate. The results showed that the rates of bio-slurry affected the rate of increase in carrot leaf length and did not significantly affect the other parameters or yield of carrot plants in the lowlands. Rates of 10 tons/ha and 20 tons/ha produced a higher leaf length than 15 tons / ha. The media volumes influenced the rate of increase in leaf length, rate of increase in the number of leaves, plant fresh weight, dry tap root weight and tap root length. The media volume of 5000 cm3 and 7000 cm3 resulted higher growth and yield of carrot plants in the lowlands rates of the media volume of 2000 cm3 and 4000 cm3. There was no interaction between the bio-slurry rates and the media volumes in influencing the growth and yield of carrot plants in the lowland